Accuracy of Speed Trials on the Measured Mile - Verstelle, J. Th. (The International Hydrographic Review, 2018)
Speed over the ground S is determined from observations of the time interval between the perpendicular crossing of two parallel lines of beacons, usually exactly one nautical mile apart. The combined effect of observational errors is investigated. It is shown that — contrary to a widely held opinion — these effects are not negligible. The required speed through the water V is determined by the usual method of taking the mean of means of at least 4 determinations of S on opposite courses. The reliability of this method of elimination of drift is not a subject of discussion in this News Letter; it is however shown that the standard error in V is considerably smaller than in each of the 4 determinations of S. Trials in daytime are to be preferred, because night trials are likely to be considerably less accurate. Other methods of speed trials are discussed in News Letter No. 27, 1958 (*).